2018
DOI: 10.3390/min8090408
|View full text |Cite
|
Sign up to set email alerts
|

Structural Control on Clay Mineral Authigenesis in Faulted Arkosic Sandstone of the Rio do Peixe Basin, Brazil

Abstract: Clay minerals in structurally complex settings influence fault zone behavior and characteristics such as permeability and frictional properties. This work aims to understand the role of fault zones on clay authigenesis in arkosic, high-porosity sandstones of the Cretaceous Rio do Peixe basin, northeast Brazil. We integrated field, petrographic and scanning electron microscopy (SEM) observations with X-ray diffraction data (bulk and clay-size fractions). Fault zones in the field are characterized by low-porosit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Based on X‐ray diffraction analysis of clay minerals of outcrop samples, Maciel et al. (2018) suggested that the three formations experienced a maximum burial depth of <1–2 km.…”
Section: Geological Settingsmentioning
confidence: 99%
“…Based on X‐ray diffraction analysis of clay minerals of outcrop samples, Maciel et al. (2018) suggested that the three formations experienced a maximum burial depth of <1–2 km.…”
Section: Geological Settingsmentioning
confidence: 99%
“…In the domain of economic geology, faults are fundamental structures that can have two contrasting behaviours: (i) Hydrogeological barriers that help the concentration of ore, as demonstrated by the contribution of Grare et al [26] in the case of the Kiggavik uranium example (Canada), and (ii) a zone of permeability that can favour fluid circulation and can serve as a guide for the mineralisation trapping. The work of Maciel et al [27] proposes a surprising example in which fault occurrences have a negative role for clay authigenesis efficiency; this work also discusses the consequence on reservoir characteristics. Sun et al [28] end the section on relations with brittle tectonics by presenting an innovative GIS-based spatial analysis of mineral deposit patterns in correlation with detailed structural features, in order to propose some implications on Structural Control.…”
mentioning
confidence: 94%
“…A clay mineral approach can be used to recognize the deformation condition according to their physical properties [2]. Clay minerals have essential relevance to geological studies such as fault gouge, weathering, landslides and geotechnical engineering [3][4][5][6][7][8]. Clay minerals can be produced by weathering and hydrothermal alteration [9,10].…”
Section: Introductionmentioning
confidence: 99%